2019
DOI: 10.1002/er.4616
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simulation of transport processes within blended electrodes on the particle scale

Abstract: Summary An electrochemical model that is capable to simulate charge and species transport within the three‐dimensional particulate cathode structure of lithium‐ion battery half‐cells is applied to blended electrodes. The electrodes are assumed to consist of physical mixtures of LiMn2O4 (LMO) and Li[Ni1/3Co1/3Mn1/3]O2 (NMC) as cathode active materials. The results of the numerical simulations reveal that there is a significant temporal variation in the distribution of the intercalation current between the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…[14] Supported by simulation studies, the different working potentials result in significantly higher stress of one material at a given potential and the performance of the blend is negatively affected. [15] In contrast to these studies, blend electrodes are generally reported to show advantageous electrochemical performance. As frequently reported, particle-particle interactions of different active materials lead to synergistic effects within the electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Supported by simulation studies, the different working potentials result in significantly higher stress of one material at a given potential and the performance of the blend is negatively affected. [15] In contrast to these studies, blend electrodes are generally reported to show advantageous electrochemical performance. As frequently reported, particle-particle interactions of different active materials lead to synergistic effects within the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…used a model system without intermixed particles to show that the currents applied during charge and discharge are inhomogenously distributed among the different electroactive materials [14] . Supported by simulation studies, the different working potentials result in significantly higher stress of one material at a given potential and the performance of the blend is negatively affected [15] . In contrast to these studies, blend electrodes are generally reported to show advantageous electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…11 Dai et al reported that the stress level in LiMn 2 O 4 (LMO) particles can be reduced by blending in LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) particles. 12 However, since the single and P2D models are limited in capturing the complex microstructural characteristics of electrodes, electrochemical models that combine with the two-dimensional (2D) 13 or three-dimensional (3D) electrode model 14 have been proposed. For example, Xu et al developed a three-dimensional electrode particle model to explain the relationship between mechanical failure and impedance increase.…”
Section: Introductionmentioning
confidence: 99%
“…In this publication, the electrochemical model published by Kespe et al [17][18][19] is used. It consists of two nonoverlapping domains and considers the charge and mass transport in a spatially resolved positive electrode.…”
Section: Electrochemical Modelmentioning
confidence: 99%
“…The focus was mainly on mechanical degradation. Kespe et al [17][18][19] developed a 3D model taking into account periodic electrode structures consisting of smooth and spherical particles, whereby different particle sizes, the electrode structure, the carbon black distribution and blended cathodes were used to derive recommendations for optimized manufacturing processes. Mistry et al 20 investigated the complex interaction of the electrochemically coupled transport processes using spherical AM particles and the effect of the carbon black morphology and electrode porosity on battery performance.…”
Section: Introductionmentioning
confidence: 99%